"Forms" of water mites (Acari: Hydrachnidia): intraspecific variation or valid species?. Issue 10 (28th August 2013) - Stålstedt, Jeanette; Bergsten, Johannes; Ronquist, Fredrik
Abstract In many groups of organisms, especially in the older literature, it has been common practice to recognize sympatrically occurring phenotypic variants of a species as "forms". However, what these forms really represent often remains unclear, especially in poorly studied groups. With new algorithms for DNA‐based species delimitation, the status of forms can be explicitly tested with molecular data. In this study, we test a number of what is now recognized as valid species of water mites (Hydrachnidia), but have in the past been treated as forms sympatrically occurring with their nominate species. We also test a form without prior taxonomical status, using DNA and morphometrics. The barcoding fragment of COI, nuclear 28S and quantitative analyses of morphological data were used to test whether these taxa merit species status, as suggested by several taxonomists. Our results confirm valid species. Genetic distances between the form and nominate species (Piona dispersa and Piona variabilis, COI 11%), as well as likelihood ratio tests under the general mixed‐Yule coalescent model, supported that these are separately evolving lineages as defined by the unified species concept. In addition, they can be diagnosed with morphological characters. The study also reveals that some taxa genetically represent more than one species. We propose that P. dispersa are recognized as valid taxa at the species level. Unionicola minor (which may consist of several species), Piona stjordalensis, P. imminuta s. lat., and P. rotundoides are confirmed as species using this model. The results also imply that future studies of other water mite species complexes are likely to reveal many more genetically and morphologically distinct species.